Acetyl-l-carnitine increases mitochondrial protein acetylation in the aged rat heart. (January 2015) - Kerner, Janos; Yohannes, Elizabeth; Lee, Kwangwon; Virmani, Ashraf; Koverech, Aleardo; Cavazza, Claudio; Chance, Mark R.; Hoppel, Charles
Highlights: Acetylcarnitine administration reverses the age-induced mitochondrial defect. In vivo acetylcarnitine treatment increases mitochondrial protein acetylation. Acetylcarnitine affects mitochondrial protein expression and enzyme activity. Abstract: Previously we showed that in vivo treatment of elderly Fisher 344 rats with acetylcarnitine abolished the age-associated defect in respiratory chain complex III in interfibrillar mitochondria and improved the functional recovery of the ischemic/reperfused heart. Herein, we explored mitochondrial protein acetylation as a possible mechanism for acetylcarnitine's effect. In vivo treatment of elderly rats with acetylcarnitine restored cardiac acetylcarnitine content and increased mitochondrial protein lysine acetylation and increased the number of lysine-acetylated proteins in cardiac subsarcolemmal and interfibrillar mitochondria. Enzymes of the tricarboxylic acid cycle, mitochondrial β-oxidation, and ATP synthase of the respiratory chain showed the greatest acetylation. Acetylation of isocitrate dehydrogenase, long-chain acyl-CoA dehydrogenase, complex V, and aspartate aminotransferase was accompanied by decreased catalytic activity. Several proteins were found to be acetylated only after treatment with acetylcarnitine, suggesting that exogenous acetylcarnitine served as the acetyl-donor. Two-dimensional fluorescence difference gel electrophoresis analysis revealed that acetylcarnitine treatment also induced changes in mitochondrial protein amount; a two-fold or greater increase/decrease in abundance was observed for thirty one proteins. Collectively, our data provide evidence for the first time that in the aged rat heart in vivo administration of acetylcarnitine provides acetyl groups for protein acetylation and affects the amount of mitochondrial proteins.